Effect Of Catalysts On The Formation Of Titanium Hydride Under Hydrogen Atmopshere - Wong, Jia Ying (Universiti Sains Malaysia, 2018)
The research objective is to produce titanium hydride (TiH2) from the reaction between magnesium Hydride (MgH2) and titanium tetrachloride (TiCl4) under hydrogen atmosphere using catalysts such as nickel (Ni), ammonium chloride (NH4Cl) and calcium fluoride (CaF2). The experiment was performed by design of experiment (DOE). The parameters involved were reaction temperature (300 to 400 oC), reaction time (60 to 120 minutes) and molar ratio of Ni to NH4Cl (0.1 to 0.3) while the responses were percentage of weight gain and degree of dehydriding. Various characterization method had been carried out such as X-Ray Diffraction (XRD), Field Emission Scanning Electron Microscopy (FESEM),Energy Dispersive X-Ray Spectroscopy (EDS), Fourier-transform infrared spectroscopy (FTIR), CHNS elemental analysis and Inductively Coupled Plasma Optical Emission Spectrometry (ICP-OES). From the experimental results, the high percentage of weight gain of 17 % was achieved at the reaction temperature of 400 oC, 60 minutes of reaction time and molar ratio of Ni to NH4Cl of 0.5 while highest degree of dehydriding of 79.85% was obtained when reaction temperature was 300 oC, reaction time was 120 minutes and molar ratio of Ni to NH4Cl was 1.5. The DOE analysis showed that reaction time was the most significant parameter, followed by reaction temperature and molar ratio of Ni to NH4Cl. The main compound formed after the reaction was magnesium nickel instead of titanium hydride because the amount of the nickel catalyst used was large while the amount of titanium tetrachloride gas flow inside the tube furnace was too little. Besides, the existence of reverse reaction and high reaction temperature caused the desorption of magnesium hydride by nickel under hydrogen atmosphere, forming magnesium nickel. From the simulation results, the isothermal and non-isothermal Shrinking Core Model (SCM) were used to study the reaction. Both isothermal and non-isothermal shrinking core model showed similar trend and significant closeness to the experimental result within reaction time of 60 minutes.